Pengaruh Massa Terhadap Kapasitas Adsorpsi Komposit Berbahan Spent Bleaching Earth (SBE) – Spent Mushroom Substrate (SMS) Sebagai Adsorben Logam Cu2+ - Ryan Renaldi; Elvi Yenie; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Heavy metal pollution is found a lot in the environment, One of the alternative to reducing heavy metals from industrial waste by using adsorbent composite made from Spent Bleaching Earth (SBE) and Spent Mushroom Substrate (SMS). This study aims to determine adsorption capacity of the SBE-SMS composite against Cu2+ metal ion. This study used variation mass adsorbent 1, 3, 5, 7 dan 9 (gram), and contact time adsorption 60 minute. With adsorbent composition 25% SBE and 75% SMS, concentration artificial solvent Cu 20 mg/L, pH 5 and stirring speed 60 rpm obtained highest adsorption capacity was obtained at a mass of 1 grams with a capacity value of 2,9948 mg/g and the lowest adsorption capacity at a mass of 9 grams with a capacity value of 0,6568 mg/g.Key words: Adsorption, Composite, Spent Bleaching Earth, Spent Mushroom Substrate, Cu2+